Man of Marble - Czlowiek z marmuru - Andrzej Wajda (1977)
In 1976, a young woman in Krakow is making her diploma film, looking behind the scenes at the life of a 1950s bricklayer, Birkut, who was briefly a proletariat hero, at how that heroism was created, and what became of him. She gets hold of outtakes and censored footage and interviews the man's friends, ex-wife, and the filmmaker who made him a hero. A portrait of Birkut emerges: he believed in the workers' revolution, in building housing for all, and his very virtues were his undoing. Her hard-driving style and the content of the film unnerve her supervisor, who kills the project with the excuse she's over budget. Is there any way she can push the film to completion?
Keywords: Drama